Determinants of Severe Acute Malnutrition Among HIV-positive Children Receiving HAART in Public Health Institutions of North Wollo Zone, Northeastern Ethiopia: Unmatched Case–Control Study - Bimerew M; Teshome GS; Abebe F; Demis A; Baye G; Adimasu M (Dove Medical Press, 2020)
Melaku Bimerew Getahun,1 Girum Sebsibie Teshome,2 Fikrtemariam Abebe Fenta,2 Asmamaw Demis Bizuneh,1 Getaneh Baye Mulu,3 Mekonen Adimasu Kebede2 1Department of Nursing, College of Health Sciences, Woldia University, Woldia, Ethiopia; 2School of Nursing and Midwifery, College of Health Science, Addis Ababa University, Addis Ababa, Ethiopia; 3Department of Nursing, College of Health Sciences, Debre Birhan University, Debre Birhan, EthiopiaCorrespondence: Melaku Bimerew Getahun Tel +251-923065826Email mebiget@gmail.comBackground: Over half of the children living with HIV/AIDS suffer from severe acute malnutrition especially in countries having food insecurity like Ethiopia. However, determinants of severe acute malnutrition among HIV-positive children receiving care and treatment in antiretroviral therapy clinics in Ethiopia are not abundantly investigated. The aim of this study was to assess the determinants of severe acute malnutrition among HIV-positive children receiving highly active antiretroviral therapy in public health institutions of the North Wollo Zone, Northeastern Ethiopia.Methods: An institutional-based unmatched case–control study was conducted on 204 under-fifteen, HIV-positive children (68 cases and 136 controls). The data were collected by reviewing medical records and by interviewing attendants. Binary and multiple logistic regressions were employed, and odds ratio with 95%CI was used to interpret results. A p-value of < 0.05 was considered as a significant difference between cases and controls for the exposure variable of interest.Results: A total of 204 under-fifteen, HIV-positive children were included in this study. Of them, 49.5% were males. About 79.4% of those children had acquired HIV infection through vertical transmission. Poor adherence to ART Adj-OR: 5.72 (1.08– 30.27), duration on ART Adj-OR: 5.54 (1.44– 21.24), severe immunodeficiency Adj-OR: 6.41 (1.09– 37.86), advanced WHO clinical stage Adj-OR: 3.58 (1.03– 12.43), oropharyngeal disease Adj-OR: 4.72 (1.13– 19.73) and chronic diarrhea Adj-OR: 3.98 (1.05– 15.04) were identified to be determinants of SAM in those children.Conclusion: Determinant factors for SAM among HIV-positive children were chronic diarrhea, severe immunodeficiency, duration and adherence to ART, oropharyngeal disease and advanced WHO clinical stage. Therefore, it is better if interventions are developed and implemented to address these identified factors.Keywords: HIV-positive children, severe acute malnutrition, determinants